The Production of Standardized Samples with Known Concentrations for Severe Acute Respiratory Syndrome Coronavirus 2 RT-qPCR Testing Validation for Developing Countries in the Period of the Pandemic Era. (3rd August 2021) - Cuong, Hoang Quoc; Hai, Nguyen Duc; Linh, Hoang Thuy; Hieu, Nguyen Trung; Anh, Nguyen Hoang; Ton, Tran; Dong, Tran Cat; Thao, Vu Thanh; Tuoi, Do Thi Hong; Tuan, Nguyen Duc; Loan, Huynh Thi Kim; Long, Nguyen Thanh; et al.
Abstract : Background . Severe acute respiratory syndrome coronavirus 2 ( SARS-CoV-2 ) has caused a pandemic of pneumonia spreading around the world, leading to serious threats to public health and attracting enormous attention. There is an urgent need for sensitive diagnostic testing implementation to control and manage SARS-CoV-2 in public health laboratories. The quantitative reverse transcription PCR (RT-qPCR) assay is the gold standard method, but the sensitivity and specificity of SARS-CoV-2 testing are dependent on a number of factors. Methods . We synthesized RNA based on the genes published to estimate the concentration of inactivated virus samples in a biosafety level 3 laboratory. The limit of detection (LOD), linearity, accuracy, and precision were evaluated according to the bioanalytical method validation guidelines. Results . We found that the LOD reached around 3 copies/reaction. Furthermore, intra-assay precision, accuracy, and linearity met the accepted criterion with an RSD for copies of less than 25%, and linear regression met the accepted R 2 of 0.98. Conclusions . We suggest that synthesized RNA based on the database of the NCBI gene bank for estimating the concentration of inactivated virus samples provides a potential opportunity for reliable testing to diagnose coronavirus disease 2019 (COVID-19) as well as limit the spread of the disease. This method may be relatively quick and inexpensive, and it may be useful for developing countries during the pandemic era. In the long term, it is also applicable for evaluation, verification, validation, and external quality assessment.